2024
DOI: 10.1186/s12934-024-02304-5
|View full text |Cite
|
Sign up to set email alerts
|

Production and secretion of recombinant spider silk in Bacillus megaterium

Alexander Connor,
R. Helen Zha,
Mattheos Koffas

Abstract: Background Silk proteins have emerged as versatile biomaterials with unique chemical and physical properties, making them appealing for various applications. Among them, spider silk, known for its exceptional mechanical strength, has attracted considerable attention. Recombinant production of spider silk represents the most promising route towards its scaled production; however, challenges persist within the upstream optimization of host organisms, including toxicity and low yields. The high co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…This reduces metabolic burden on the cells [ 39 ], leading to an increase in cell mass and, consequently, an increase in the yield of recombinant protein. A recent study also demonstrated increased recombinant MA silk expression yields in Bacillus megaterium through targeted amino acid supplementation in minimal medium [ 40 ], implying that this is a more generally useful strategy for different expression hosts and silks. Notably, the molecular weight of Py 2 W 2 is ∼86.4 kDa meaning that this approach proved successful in increasing the yield of a relatively large-sized recombinant silk protein.…”
Section: Resultsmentioning
confidence: 99%
“…This reduces metabolic burden on the cells [ 39 ], leading to an increase in cell mass and, consequently, an increase in the yield of recombinant protein. A recent study also demonstrated increased recombinant MA silk expression yields in Bacillus megaterium through targeted amino acid supplementation in minimal medium [ 40 ], implying that this is a more generally useful strategy for different expression hosts and silks. Notably, the molecular weight of Py 2 W 2 is ∼86.4 kDa meaning that this approach proved successful in increasing the yield of a relatively large-sized recombinant silk protein.…”
Section: Resultsmentioning
confidence: 99%